ANALISIS UPAH MINIMUM, TINGKAT PENGANGGURAN TERBUKA, DAN JUMLAH PENDUDUK MISKIN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN PROBOLINGGO - Pingkan Syabila Tri Indiati; Kiky Asmara; Fauzatul Laily Nisa (Universitas Nias Raya, 2025)
This study aims to analyze the influence of minimum wage, open unemployment rate, and the number of poor people on the Human Development Index (HDI) in Probolinggo Regency during the period 2013–2023. A quantitative approach was employed, using multiple linear regression analysis with the assistance of SPSS version 27 software. The partial test results show that the minimum wage variable has a positive and significant effect on HDI, indicating that an increase in the minimum wage contributes to improving the quality of life. Meanwhile, the open unemployment rate has a negative but insignificant effect on HDI, suggesting that a lower unemployment rate does not necessarily reflect improved societal welfare. On the other hand, the number of poor people has a negative and significant effect on HDI, meaning that higher poverty levels are associated with lower human development quality. The regression model used in this study has an adjusted R² value of 97.3%, indicating that the three independent variables collectively explain 97.3% of the variation in HDI in Probolinggo Regency. These findings highlight that increasing the minimum wage and reducing poverty are key strategies in enhancing human development. Therefore, local government policies should focus on improving household income, eradicating poverty, and enhancing access to and quality of education and healthcare services.